2008
DOI: 10.1016/j.icarus.2008.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory studies into the effect of regolith on planetary X-ray fluorescence spectroscopy

Abstract: Laboratory studies into the effect of regolith on planetary X-ray fluorescence spectroscopy. Icarus, Elsevier, 2008, 198 (2) This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 31 publications
(29 reference statements)
0
11
0
Order By: Relevance
“…The observed XRF intensity get affected by the distribution of particle size, as the mean free path of soft X-rays is smaller than the mean particle size of lunar regolith. Laboratory experiments by (Maruyama et al, 2008;Näränen et al, 2008) shows that XRF intensity decreases with increasing phase angles (angle between source-surface-detector) and increases with decreasing size of particles. However, this effect is expected to be small on C1XS results where the ground pixel dimensions are large (hundreds of km) and considers a large distribution of particle sizes (Weider et al, 2012).…”
Section: Deriving Elemental Abundancesmentioning
confidence: 99%
“…The observed XRF intensity get affected by the distribution of particle size, as the mean free path of soft X-rays is smaller than the mean particle size of lunar regolith. Laboratory experiments by (Maruyama et al, 2008;Näränen et al, 2008) shows that XRF intensity decreases with increasing phase angles (angle between source-surface-detector) and increases with decreasing size of particles. However, this effect is expected to be small on C1XS results where the ground pixel dimensions are large (hundreds of km) and considers a large distribution of particle sizes (Weider et al, 2012).…”
Section: Deriving Elemental Abundancesmentioning
confidence: 99%
“…All other elemental abundances are therefore assessed against the fixed Si (21 wt %; Prettyman et al, 2006) and are expressed as elemental ratios (i.e., Mg/Si and Al/Si). This normalisation largely cancels out inaccuracies in the results caused by calibration uncertainties and variations in XRF intensity that are related to physical and compositional heterogeneities in the regolith (Clark and Trombka, 1997;Maruyama et al, 2008;Näränen et al, 2008;Weider et al, 2011). Theoretical and experimental investigations of XRF geometry effects (e.g., Maruyama et al, 2008;Näränen et al, 2008;Parvianen et al, 2011;Weider et al, 2011) have shown that it can be problematic to express XRF-derived abundances as ratios of two elements that differ significantly in energy (e.g., Si and Fe).…”
Section: Si Normalisationmentioning
confidence: 99%
“…X-ray fluorescence intensity depends on a variety of factors other than solar x-ray spectra such as particle size, geometry of observation and the mineral matrix (Maruyama et al, 2008;Naranen et al, 2008;. It is very difficult to deconvolve the absolute flux from lunar elements uniquely given the multi parameter dependencies.…”
Section: Xrf Intensity: Dependenciesmentioning
confidence: 99%